Pengaruh Good Corporate Governance Terhadap Manajemen Laba - Fieska Putri Setiani; Ngurah Pandji MAD (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This study aims to analyze the effect of institutional ownership, managerial ownership, size of the board of commissioners, the proportion of independent commissioners and audit committees on the earnings management of companies included in the JII (Jakarta Islamic Index) 2017-2020. The sample method used in this research is purposive sampling method, namely the sampling method based on certain criteria. The sample that meets the criteria in this study is 44 company data included in the JII (Jakarta Islamic Index) 2017-2020. The analytical method used in this research is multiple linear regression analysis which is preceded by the classical assumption test consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. While the hypothesis testing is done by using the F test and t test. The results of data analysis or regression results show that partially institutional and managerial ownership has a significant effect on earnings management. The value of the coefficient of determination is 26.2%.